Analysis of Work-Life Balance, Organizational Culture, and Work Motivation on Employee Performance at PT Perkebunan Nusantara IV Medan - Dina Amara Novita Sari; Teguh Wahyono; Ikhah Malikhah (International Journal of Management, Economic and Accounting, 2024)
This study aims to determine the influence of work-life balance, organizational culture, and work motivation on employee performance at PT Perkebunan Nusantara IV Medan. The object of this study is the employees of PT Perkebunan Nusantara IV Medan. The research was conducted in 2023-2024. The population and sample of this study amounted to 76 respondents. Data processing was done using SPSS version 24. The data tests conducted included the classical assumption test and multiple linear regression. The results showed that the t-test for the work-life balance variable (X1) had a t-value of 2.353 > t-table of 1.993 with a significance value of 0.021 < 0.05, meaning the work-life balance variable partially has a positive and significant effect on employee performance. The t-test results for the organizational culture variable (X2) showed a t-value of 10.624 > t-table of 1.993 with a significance value of 0.000 < 0.05, indicating that the organizational culture variable partially has a positive and significant effect on employee performance. The t-test results for the work motivation variable (X3) showed a t-value of 9.395 > t-table of 1.993 with a significance value of 0.000 < 0.05, indicating that the work motivation variable partially has a positive and significant effect on employee performance. The F-test results showed an F-value of 121.388 > F-table of 3.12 with a significance value of 0.000 < 0.05. The R2 test results of 0.828 or 82.8% indicate that the independent variables work-life balance, organizational culture, and work motivation can explain the dependent variable of employee performance.